1976
DOI: 10.1111/j.1399-6576.1976.tb05040.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermittent Positive Pressure Ventilation on Cardiac Systolic Time Intervals

Abstract: The measurement of systolic time intervals (STI) has been widely used as a non-invasive method of assessing the inotropic state of the heart, and normal values are available for healthy individuals breathing spontaneously. The present study was performed in order to evaluate how intermittent positive pressure ventilation (IPPV) affects STI. Ten subjects were investigated before and during halothane anaesthesia for routine surgery. Oesophageal pressure, respiratory minute volume and frequency, arterial blood-ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Several human studies have also found that decreased PEP after fluid challenge is associated with increase in stroke volume (10,13,18). Interestingly, Brundin et al (9) demonstrated that intermittent positive pressure ventilation increased PEP by the reduction of venous return and thus stroke volume. In the present study, ⌬PEP was used as an index of preload responsiveness, with the hypothesis that, as Values are means Ϯ SD.…”
Section: Discussionmentioning
confidence: 99%
“…Several human studies have also found that decreased PEP after fluid challenge is associated with increase in stroke volume (10,13,18). Interestingly, Brundin et al (9) demonstrated that intermittent positive pressure ventilation increased PEP by the reduction of venous return and thus stroke volume. In the present study, ⌬PEP was used as an index of preload responsiveness, with the hypothesis that, as Values are means Ϯ SD.…”
Section: Discussionmentioning
confidence: 99%
“…We also need to consider other causes for the shortening of PTT unrelated to a direct effect of sympathetic tone on PTT. The increased abdominal pressure may have affected PTT either via changes in preload (causing a shortening of PEP) or due to the requirement for higher intrathoracic pressures for a given tidal volume [13][14][15]. A higher intrathoracic pressure will affect PTT by changing PEP as well as by changing the compliance of the arterial blood vessels [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Several human studies have also found that decreased PEP after fluid challenge is associated with increase in stroke volume. [12][13][14] Interestingly, Brundin et al 15 demonstrated that intermittent-positive pressure ventilation increased PEP by the reduction of venous return and thus stroke volume. As already stated, ⌬PEP was used as a gauge of volume status hypothesizing that as PPV; ⌬PEP is a relative and not absolute index related to positive pressure breath that induces change in ventricular stroke volume related to change in ventricular preload.…”
Section: Discussionmentioning
confidence: 98%